153k views
1 vote
25x2 −36y 8 25, x, squared, minus, 36, y, start superscript, 8, end superscript We can factor the expression as (U+V)(U-V)(U+V)(U−V)left parenthesis, U, plus, V, right parenthesis, left parenthesis, U, minus, V, right parenthesis where UUU and VVV are either constant integers or single-variable expressions. What are UUU and VVV?

User Mpe
by
5.6k points

1 Answer

6 votes

Answer:


(5x + 6y^4)(5x - 6y^4)

Explanation:

Given the expression:


25x^2 -36y^8

We are to express it as difference of two square (u+v)(u-v). According to the rule:


u^2 - v^2 = (u+v)(u-v)

We need to express
25x^2 -36y^8 as difference of squares and this is as shown:


= 25x^2 -36y^8\\= 5^2x^2 - 6^2(y^4)^2\\= (5x)^2 -(6y^4)^2\\

From the resulting expression we can say:


u = 5x \ and \ v = 6y^4

If we substitute in the rule above we will have:


= (5x)^2 -(6y^4)^2\\= (5x + 6y^4)(5x - 6y^4)

Hence the expression expressed as difference of two square is:


(5x + 6y^4)(5x - 6y^4)

User Duncan Finney
by
5.0k points